2019
DOI: 10.1016/j.apsb.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin alleviates endothelial gap junction dysfunction through inhibition of NLRP3 inflammasome activation in LPS-induced vascular injury

Abstract: The loss of endothelial connective integrity and endothelial barrier dysfunction can lead to increased vascular injury, which is related to the activation of endothelial inflammasomes. There are evidences that low concentrations of aspirin can effectively prevent cardiovascular diseases. We hypothesized that low-dose aspirin could ameliorate endothelial injury by inhibiting the activation of NLRP3 inflammasomes and ultimately prevent cardiovascular diseases. Microvascular endothelial cells were stimulated by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 54 publications
0
50
1
3
Order By: Relevance
“…Our data show that Ang II infusion induced the activation of NLRP3 inflammasomes in rat kidneys (Figures 2A-D). Previous studies have revealed the role of NLRP3 inflammasomes in mediating the release of HMGB1 (Lamkanfi et al, 2010;Chen et al, 2015;Zhou et al, 2019). Several reports have identified that HMGB1, a member of the high mobility group nuclear protein family, acts as a nuclear homeostasis DNA-binding protein (Paudel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that Ang II infusion induced the activation of NLRP3 inflammasomes in rat kidneys (Figures 2A-D). Previous studies have revealed the role of NLRP3 inflammasomes in mediating the release of HMGB1 (Lamkanfi et al, 2010;Chen et al, 2015;Zhou et al, 2019). Several reports have identified that HMGB1, a member of the high mobility group nuclear protein family, acts as a nuclear homeostasis DNA-binding protein (Paudel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin is one of the most commonly used drugs for the secondary prevention of cardiovascular disease 104 . Zhou et al found that aspirin protects the expression of ZO-1 and ZO-2 by inhibiting NLRP3 inflammasome formation and activation in LPS-induced MVECs and coronary arterial endothelium, thereby alleviating endothelial gap junction dysfunction 105 . This study unraveled a novel mechanism of aspirin in ameliorating endothelial dysfunction by blocking redox signaling and NLRP3 inflammasome activation, providing a new viewpoint on the clinical potential of aspirin in the early prevention of cardiovascular diseases 105 .…”
Section: Other Anti-inflammatory or Antioxidant Drugsmentioning
confidence: 99%
“…Zhou et al found that aspirin protects the expression of ZO-1 and ZO-2 by inhibiting NLRP3 inflammasome formation and activation in LPS-induced MVECs and coronary arterial endothelium, thereby alleviating endothelial gap junction dysfunction 105 . This study unraveled a novel mechanism of aspirin in ameliorating endothelial dysfunction by blocking redox signaling and NLRP3 inflammasome activation, providing a new viewpoint on the clinical potential of aspirin in the early prevention of cardiovascular diseases 105 . The mitochondrion-targeting antioxidant mitoquinone (MitoQ) was found to inhibit endothelial inflammation and barrier injury in cigarette smoke extract (CSE)-treated HUVECs via restoring mitochondrial damage 106 .…”
Section: Clinical Drugs and Nlrp3 Inflammasome And Endothelial Dysfunmentioning
confidence: 99%
“…For immunofluorescence, the sections were incubated with anti-F4/80 (1:100) plus anti-NLRP3 (1:100) or anti-caspase-1 (1:100) antibodies overnight. On the next day, the slides were washed and labeled with corresponding conjugated secondary antibodies (Alexa Fluor 488 and Dylight 594) for 2 h. Then, slides were visualized sequentially using a laser scanning confocal microscope (ZEN2.3, Zeiss) [ 30 , 31 ]. Settings for image acquisition were identical for both control and experimental tissues.…”
Section: Methodsmentioning
confidence: 99%